Grain boundary engineering in roll-bonded copper to overcome the strength-ductility dilemma - Taali, Saeed; Toroghinejad, Mohammad Reza; Kuglstatter, Moritz; Höppel, Heinz Werner (Journal of Materials Research and Technology, 2022)
Copper sheets with graded and fine-grained (FG) microstructures were processed by accumulative roll bonding (ARB) and subsequent annealing to evaluate the effect of structural heterogeneities on the strength-ductility relationship. By an appropriate design of the individual ARB-process-steps, two types of graded structures (GSs) have been achieved where the grain size gradually changes from a more refined grain structure at the surface to a coarser one in the interior (CGC) or a coarser one at the surface to a finer one in the interior (FGC). For both types, the grains size gradually changes between 4 and 19 microns across the thickness of samples. In terms of the uniform tensile work, GSs exhibited a superior combination of strength and elongation owing to the heterodeformation induced strengthening. In addition to a good strain delocalization capability compared to their coarse-grained (CG) counterpart, the graded microstructures affect the crack paths in the non-uniform deformation regime.(c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
CRIS-Team WoS Importer:2022-05-13